2011
DOI: 10.1007/s00253-011-3090-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analyses of ammonia-oxidizing Archaea and bacteria in the sediments of four nitrogen-rich wetlands in China

Abstract: With the rapid development of ammoniasynthesizing industry, the ammonia-nitrogen pollution in wetlands acting as the sink of point and diffuse pollution has been increased dramatically. Most of ammonia-nitrogen is oxidized at least once by ammonia-oxidizing prokaryotes to complete the nitrogen cycle. Current research findings have expanded the known ammonia-oxidizing prokaryotes from the domain Bacteria to Archaea. However, in the complex wetlands environment, it remains unclear whether ammonia oxidation is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
4
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 37 publications
3
50
4
2
Order By: Relevance
“…As NH 4 þ , NO 3 À and DOC concentrations decreased N 2 O fluxes declined in all microcosms because electron donors and acceptors for microbial N 2 O formation became limiting. The significantly lower N 2 O emissions from biochar-containing microcosms observed within the first week (Figure 1b, Supplementary Figure S2b) agree with the findings of several recently published field-and laboratory-based studies using different biochars and soils (Yanai et al, 2007;Singh et al, 2010b;van Zwieten et al, 2010;Taghizadeh-Toosi et al, 2011;Wang et al, 2011b;Augustenborg et al, 2012;Wang et al, 2012;Zheng et al, 2012;Zhang et al, 2012a, b). According to these studies, the most important environmental factors responsible for the reduced N 2 O emissions from biochar-amended soil were: (i) limited bioavailability of electron donors and acceptors (DOC,NO 3 À and NH 4 þ ) for microbial nitrification and denitrification due to sorption/ immobilization onto biochar particles (Singh et al, 2010b;Taghizadeh-Toosi et al, 2011;Wang et al, 2011a); (ii) improved soil aeration through biochar addition and consequently reduced denitrification (Yanai et al, 2007;van Zwieten et al, 2010;Augustenborg et al, 2012;Zhang et al, 2012b); and (iii) increased activity of N 2 O-reducing bacteria due to an elevated soil pH caused by biochar addition (van Zwieten et al, 2010;Zheng et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…As NH 4 þ , NO 3 À and DOC concentrations decreased N 2 O fluxes declined in all microcosms because electron donors and acceptors for microbial N 2 O formation became limiting. The significantly lower N 2 O emissions from biochar-containing microcosms observed within the first week (Figure 1b, Supplementary Figure S2b) agree with the findings of several recently published field-and laboratory-based studies using different biochars and soils (Yanai et al, 2007;Singh et al, 2010b;van Zwieten et al, 2010;Taghizadeh-Toosi et al, 2011;Wang et al, 2011b;Augustenborg et al, 2012;Wang et al, 2012;Zheng et al, 2012;Zhang et al, 2012a, b). According to these studies, the most important environmental factors responsible for the reduced N 2 O emissions from biochar-amended soil were: (i) limited bioavailability of electron donors and acceptors (DOC,NO 3 À and NH 4 þ ) for microbial nitrification and denitrification due to sorption/ immobilization onto biochar particles (Singh et al, 2010b;Taghizadeh-Toosi et al, 2011;Wang et al, 2011a); (ii) improved soil aeration through biochar addition and consequently reduced denitrification (Yanai et al, 2007;van Zwieten et al, 2010;Augustenborg et al, 2012;Zhang et al, 2012b); and (iii) increased activity of N 2 O-reducing bacteria due to an elevated soil pH caused by biochar addition (van Zwieten et al, 2010;Zheng et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we confirmed that the sites near the land/water interface (0.5-2 m) showed higher potential nitrification rates (4.4 and 6.1 μg NO 2 − -N/(g dws·hr) in sites C and B, respectively compared with 1.0-1.7 μg NO 2 − -N/(g dws·hr) in other sites, Fig. 2) which were within the range of field data in other wetlands (1.0-11.3 μg NO 2 − -N/(g dws·hr)) (Herrmann et al, 2008;Wang et al, 2011). In transition areas, substantial increase of enzyme activity, microbe numbers and oxygen consumption have been observed where the subsurface flow paths and roots encountered each other (McClain et al, 2003).…”
Section: Discussionsupporting
confidence: 61%
“…The compositions and relative abundance of ammonia oxidizing archaea (AOA) and ammonia oxidizing bacteria (AOB) vary widely in many environments (Leininger et al, 2006;Wuchter et al, 2006;Di et al, 2009;Höfferle et al, 2010;Wang et al, 2011), but a consensus is that AOA may be important actors in the N cycle under unfavorable environmental conditions, e.g., limited nutrient availability, extreme pH/salinity or sulfide-containing environments (Erguder et al, 2009). However, the contribution to nitrification of AOA versus AOB remains less certain.…”
Section: Introductionmentioning
confidence: 99%
“…To get more detailed information on the potential of a combined nitrification-anammox process in the paddy soil core, qPCR assays on bacterial and archaeal amoA genes were performed according to the method in reference of Wang et al (2011). The qPCR data showed that in the root zone, ammoniaoxidizing bacteria dominated the nitrification process in agreement with the nitrification rates, and the bacterial amoA gene numbers ranged from 8.8 Â 10 5 to 3.2 Â 10 8 g À1 dry soil (Figure 5b).…”
Section: Quantitive Analysis Of Various N Cycle Processesmentioning
confidence: 99%